An Approach to Motor Winding Optimization for HEFS Machine-Based Integrated On-Board Charging Systems - Minghao Tong; Yudong Chen; Le Sun (World Electric Vehicle Journal)
In this article, to enhance the power output capability and system efficiency during charging, an approach to motor winding optimization for HEFS machine-based integrated on-board charging systems is proposed and analyzed. Firstly, the design process of the HEFS motor and the power electromagnetic components are analyzed to find the entry point for the integrated system optimization. Then, the comprehensive optimization process for the winding parameters of the HEFS motors in the integrated charging system is presented. Moreover, an integrated system based on a five-phase HEFS motor is used as an example for simulation verification. Finally, an experimental platform is built based on a 5 kW five-phase HEFS prototype. The experimental results are consistent with the simulation results. Therefore, the proposed comprehensive optimization method for windings can make the motor more suitable for building an integrated on-board charging system without affecting the electromagnetic performance of the motor. The optimization results indicate an improvement in output power and efficiency of the system in charging mode.